Is polycystic ovary syndrome associated with high sympathetic nerve activity and size at birth? - Sverrisdóttir, Y; Mogren, T; Kataoka, J; Janson, P; Stener-Victorin, E (2008)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disturbance among women of reproductive age and is proposed to be linked with size at birth and increased prevalence of cardiovascular disease. A disturbance in the sympathetic nervous system may contribute to the etiology of PCOS. This study evaluates sympathetic outflow in PCOS and its relation to size at birth. Directly recorded sympathetic nerve activity to the muscle vascular bed (MSNA) was obtained in 20 women with PCOS and in 18 matched controls. Ovarian ultrasonographic evaluation, biometric, hormonal, and biochemical parameters were measured, and birth data were collected. Women with PCOS had increased MSNA (30 +/- 8 vs. 20 +/- 7 burst frequency, P < 0.0005) compared with controls. MSNA was positively related to testosterone (r = 0.63, P < 0.005) and cholesterol (r = 0.55, P = 0.01) levels in PCOS, which, in turn, were not related to each other. Testosterone level was a stronger predictor of MSNA than cholesterol. Birth size did not differ between the study groups. This is the first study to directly address sympathetic nerve activity in women with PCOS and shows that PCOS is associated with high MSNA. Testosterone and cholesterol levels are identified as independent predictors of MSNA in PCOS, although testosterone has a stronger impact. The increased MSNA in PCOS may contribute to the increased cardiovascular risk and etiology of the condition. In this study, PCOS was not related to size at birth.